The Emperor’s old clothes: a critical review of circular fashion in gray literature - Hussain, Talia; Kuzmina, Ksenija; Koria, Mikko (Frontiers in Sustainability, 2025)
A consensus across industry, academics, and policy-makers holds that a circular fashion system can reduce pollution and waste while producing continued economic growth. Gray literature, understood here as reports published outside of academic journals, has been foundational to describing and promoting circular economy and circular fashion. Yet, this literature is rarely subjected to critical scrutiny, allowing evidence, claims and methods to go unexamined. This review aims to understand how value and the market are conceptualized in a circular fashion system, and what are the implications of this. The study employs a problematizing review of 20 gray literature documents, including a key text of circular fashion: the Ellen MacArthur Foundation’s 2017 report A New Textiles Economy: Redesigning Fashion’s Future. Textual analysis is used to identify assumptions, inferences and problem framings in the texts. These are evaluated against academic understandings, demonstrating that core concepts of the circular fashion proposal are poorly defined and unconnected to existing theory and knowledge. Existing retail practices and consumer marketing messages are central to circular fashion, while the role of the market in setting prices is ignored. A $460 billion error is revealed, refuting the claim that a circular fashion system provides an opportunity for growth. We offer a critical perspective on the role of gray literature and gray publishers in shaping policy-making and, subsequently, academic research programs. We argue that new proposals for sustainable fashion are needed, based on established knowledge and validated models.